OB Nest randomized controlled trial: a cost comparison of reduced visit compared to traditional prenatal care - Regan N. Theiler; Yvonne Butler-Tobah; Matthew A. Hathcock; Abimbola Famuyide (BMC, 2021)
Abstract Background Traditional prenatal care includes up to 13 in person office visits, and the cost of this care is not well-described. Alternative models are being explored to better meet the needs of patients and providers. OB Nest is a telemedicine-enhanced program with a reduced frequency of in-person prenatal visits. The cost implications of connected care services added to prenatal care packages are unclear. Methods Using data from the OB Nest randomized, controlled trial we analyzed the provider and staff time associated with prenatal care in the traditional and OB Nest models. Fewer visits were required for OB Nest, but given the compensatory increase in connected care activity and supplies, the actual cost difference is not known. Nursing and provider staff time was prospectively recorded for all patients enrolled in the OB Nest clinical trial. Published 2015 national wages for healthcare workers were used to calculate the actual labor cost of providing either traditional or OB Nest prenatal care in 2015 US dollars. Overhead expenses and opportunity costs were not considered. Results Total provider cost was decreased caring for the OB Nest participants, but nursing cost was increased. OB Nest care required an average of 160.8 (+/− 45.0) minutes provider time and 237 (+/− 25.1) minutes nursing time, compared to 215.0 (+/− 71.6) and 99.6 (+/− 29.7) minutes for traditional prenatal care (P < 0.01). This translated into decreased provider cost and increased nursing cost (P < 0.01). Supply costs increased, travel costs declined, and overhead costs declined in the OB Nest model. Conclusions In this trial, labor cost for OB Nest prenatal care was 34% higher than for traditional prenatal care. The increased cost is largely attributable to additional nursing connected care time, and in some practice settings may be offset by decreased overhead costs and increased provider billing opportunities. Future efforts will be focused on development of digital solutions for some routine nursing tasks to decrease the overall cost of the model. Trial registrations ClinicalTrials.gov Identifier: NCT02082275 .